2016
DOI: 10.1016/j.apenergy.2015.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on hydrothermal liquefaction of Nannochloropsis gaditana and Chlorella sp.

Abstract: Temperature effect on hydrothermal liquefaction (HTL) of Nannochloropsis gaditana and Chlorella sp. was investigated with 10% biomass loading at HTL temperatures of 180-330 o C, and reaction time of 30 minutes. Maximum yields of 47.5% for Nannochloropsis sp. and 32.5 % biocrude oil yields for Chlorella sp. were obtained at 300 o C. The higher heating values of biocrude oils produced in this work ranged between 34 and 39 MJ/kg. 79% of energy in the Nannochloropsis sp. was recovered at 300 o C and 62% of energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…6 Increased lipid content is desirable since biocrude production has been demonstrated to come primarily from lipids, followed by proteins, and then carbohydrates. 8,27,38 Compared to other fungal species used in HTL studies, R. oligosporus contained a significantly higher lipid content than yeast Saccharomyces cerevisiae (2.7%), 30 and less than the oleaginous yeast Cryptococcus curvatus (32.8%). 32 Relative to other feedstocks used in continuous-flow HTL systems, the lipid content of R. oligosporus was comparable to that of microalgae, 12 specifically, Chlorella (25%) 8 and Nannochloropsis (28%).…”
Section: Resultsmentioning
confidence: 99%
“…6 Increased lipid content is desirable since biocrude production has been demonstrated to come primarily from lipids, followed by proteins, and then carbohydrates. 8,27,38 Compared to other fungal species used in HTL studies, R. oligosporus contained a significantly higher lipid content than yeast Saccharomyces cerevisiae (2.7%), 30 and less than the oleaginous yeast Cryptococcus curvatus (32.8%). 32 Relative to other feedstocks used in continuous-flow HTL systems, the lipid content of R. oligosporus was comparable to that of microalgae, 12 specifically, Chlorella (25%) 8 and Nannochloropsis (28%).…”
Section: Resultsmentioning
confidence: 99%
“…It is apparent that some solid product holding‐up occurs inside the continuous reactor system, especially in the cooler piping downstream of the heat recovery and the pressure let‐down stages , . Reddy et al have found an average HHV for solid residue (biochar) of 19.21 – 12.54 MJ kg −1 and 19.82 – 12.05 MJ kg −1 for Nannochloropsis gaditana and Chlorella sp., respectively. However, general observations have shown small amounts of solid residues after HTL, normally less than 10 % .…”
Section: Microalgal Htlmentioning
confidence: 99%
“…Reddy et al have found an average HHV for solid residue (biochar) of 19.21 – 12.54 MJ kg −1 and 19.82 – 12.05 MJ kg −1 for Nannochloropsis gaditana and Chlorella sp., respectively. However, general observations have shown small amounts of solid residues after HTL, normally less than 10 % . The biochar contains high amounts of the crude protein.…”
Section: Microalgal Htlmentioning
confidence: 99%
See 2 more Smart Citations